Recent wind driven high sea ice area export in the Fram Strait contributes to Arctic sea ice decline - Smedsrud, Lars Henrik; Sirevaag, Anders; Kloster, Kjell; Sorteberg, Asgeir; Sandven, Stein (The Cryosphere, 2016)
Arctic sea ice area has been decreasing for the past two decades. Apart from melting, the southward drift through Fram Strait is the main ice loss mechanism. We present high resolution sea ice drift data across 79° N from 2004 to 2010. Ice drift has been derived from radar satellite data and corresponds well with variability in local geostrophic wind. The underlying East Greenland current contributes with a constant southward speed close to 5 cm s−1, and drives around a third of the ice export. We use geostrophic winds derived from reanalysis data to calculate the Fram Strait ice area export back to 1957, finding that the sea ice area export recently is about 25% larger than during the 1960's. The increase in ice export occurred mostly during winter and is directly connected to higher southward ice drift velocities, due to stronger geostrophic winds. The increase in ice drift is large enough to counteract a decrease in ice concentration of the exported sea ice. Using storm tracking we link changes in geostrophic winds to more intense Nordic Sea low pressure systems. Annual sea ice area export likely has a significant influence on the summer sea ice variability and we find low values in the 1960's, the late 1980's and 1990's, and particularly high values during 2005–2008. The study highlights the possible role of variability in ice export as an explanatory factor for understanding the dramatic loss of Arctic sea ice during the last decades publishedVersion